Kepuasan Nasabah: Tinjauan dari Kualitas Produk dan Penerapan Nilai Islam - Yeni Yulia Ningsih; Binti Nur Asiyah (Program Studi Perbankan Syariah, IAIN Palopo, 2022)
The research in this thesis is based on the quality of products Bank Muamalat KCU Kediri can not reach all layers so that customers can only choose one of several products that exist, Sharia value in BMI is less maximally applied, it appears that the customer's needs are not a concern in financing, so it is not in accordance with the needs of real customers. This study uses a quantitative approach to this type of associative research. Sampling uses accidental sampling techniques. The data source used in this study is the main data. The measurements in this study used a likert scale. Next stage, test the data instrument with validity and reliability test, classic assumption test and Multiple Linear Regression which serves to prove the research hypothesis.The results showed (1) The quality of the product had a positive and significant effect on customer satisfaction at Bank Muamalat KCU Kediri (2) Islam value had a positive and significant effect on customer satisfaction at Bank Muamalat KCU Kediri. (3) The quality of the products, and the value of Islam, together have a positive and significant effect on customer satisfaction at Bank Muamalat KCU Kediri.